Fulfillment in Logistic Infrastructure of International Internet-Trade of Ukrainian Companies - Diachek, Vitalii; Diachek, Olga; Shuba, Tetiana (International Journal of Engineering and Technology, 2018)
The article describes the concept of fulfillment, its essence and role for ensuring effective international trade on the Internet. The structure and complex of basic and additional services of fulfillment were considered. The authors gave the specific features of fulfillment that define this type of activity. The advantages and disadvantages of fulfillment outsourcing were determined. It was justified the expediency of transferring this activity to a fulfillment operator, especially in cases when small companies and start-ups start to trade internationally. The structure and algorithm of providing fulfillment services by the operators were analyzed. Â